A Systematic Literature Review of Management Accounting Systems (MAS) in The Industry Revolution 4.0 - Yuxiao, Lou; Maelah, Ruhanita (International Journal of Accounting and Economics Studies, 2025)
Industry 4.0 encourages technologies like automation with AI, big data processing, and Internet of Things (IoT) capabilities, which fundamentally alter business operations across all industrial sectors. The modern evolution of MAS contributes to data-driven decisions and better process efficiency, which helps companies achieve a better competitive advantage. MAS leverages digital tools with systems and technologies to handle finance alongside non-financial data to support decision-making (DM) at the level of cost management, along with performance evaluation and strategic planning. Industry 4.0's growth has led to MAS definition changes that allow technology implementation for real-time monitoring and prediction analysis, and business process enhancement. A systematic evaluation of the literature examines MAS evolution by using the PRISMA framework within the framework of Industry 4.0. The review understands why businesses use digital MAS and analyzes their operation within Industry 4.0 settings and their influence on business results, as well as strategic success. It points out knowledge deficiencies as well as industry-specific challenges and opportunities that businesses encounter during their effort to unite traditional MAS with Industry 4.0 tools. It recommends performing additional investigations to identify how MAS can adapt to Industry 4.0 requirements, which will support organizations in their lasting business development.